Correlation Analysis of Spatial Distribution, Temporal Seismotectonics, and Return Period of Earthquake in East Nusa Tenggara, Indonesia. (7th July 2019) - Sianturi, Hery Leo; Susilo, Adi; Sunaryo,; Maryanto, Sukir
Abstract : This paper presents spatial distribution, temporal seismotectonics, and return period of earthquake in East Nusa Tenggara Province, Indonesia, using earthquake data and Maximum Likelihood methods. The data used are ISC, USGS/NEIC, and Indonesian Meteorology, Climatology and Geophysics Agency (IMCGA) earthquake catalog data for the period of 1918 to 2015. The results show that the a-value ranges from 5.0 to 8.5 and b-value ranges from 0.6 to 1.3. The pattern of spatial distribution of b-value is relatively low corresponding to the low of a-value, which means the high level of stress of rock in the area. The fractal dimension shows that the D value ranges from 1.384 to 1.874. The earthquake that occurred in East Nusa Tenggara Province was dominated by a small magnitude with great seismicity and the fastest return period is in Alor and Timor islands which is 44 days.